Extracellular SQSTM1 as an inflammatory mediator. Issue 12 (1st December 2020) - Zou, Borong; Liu, Jiao; Klionsky, Daniel J.; Tang, Daolin; Kang, Rui
ABSTRACT: Excessive inflammation may lead to irreparable injury and even death, but the key mediators and underlying mechanisms remain unclear. Our recent findings indicate that SQSTM1/p62 (sequestosome 1), a well-known macroautophagy/autophagy receptor, is a lethal inflammatory mediator of sepsis and septic shock. The release of SQSTM1 occurs during tissue damage or microbial invasion through two main ways: one is passive and the other is active. Passive release occurs in the context of GSDMD-mediated pyroptosis. Active SQSTM1 secretion requires two basic steps: the first step is the expression and phosphorylation of SQSTM1 mediated by STING1/STING/TMEM173, and then the unconventional secretion of SQSTM1 by secretory lysosomes. After release, the extracellular SQSTM1 binds to membrane receptor INSR to activate glycolysis, leading to subsequent production of pro-inflammatory cytokines in a transcription factor NFKB-dependent manner. Functionally, genetic deletion or pharmacological inhibition of the SQSTM1-INSR pathway limits tissue damage, systemic inflammation, organ failure, and death in experimental sepsis models in mice. Moreover, the activation of the SQSTM1-INSR pathway is related to the severity of sepsis in patients. These findings highlight a pathological role of extracellular SQSTM1 in infection, inflammation, and immunity.